(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the reforms implemented to increase the effectiveness of education in general education schools, including the introduction of the electronic information educational environment to the processes of teaching biology, are highlighted. Also, comments on the creation and implementation of electronic resources that serve to improve students’ information literacy are presented.